Development of Android Assisted E-Modules on Wireless Network Materials For Class XI Students of Computer Network Engineering - Ihsan, Iqbal Muhammad; Firdaus, Rangga; Sesunan, Feriansyah (Universitas Lampung, 2021)
This study aims to develop an Android-assisted e-Module on wireless network material for class XI students of computer and network engineering that is valid and practical. The subject of this research is class XI majoring in computer and network engineering at SMKN 1 Bandar Lampung, amount 34 people. The method used in this research is R&D with a development model which includes the steps of ADDIE analysis (preparation and needs analysis), design (designing the product to be developed), development (testing content, constructs, and media experts), product implementation (planning, preparation, teacher perception test and student readability), evaluation. This research and development resulted in a valid and practical product. This android-assisted e-Module that was developed has been validated and meets the criteria for a good and appropriate learning media to use, where the average content expert test result is 3.54, validation by constructor is 3.66 and validation test by media expert is 3, 69 with a very valid category. Android-assisted e-Modules also get very good scores from the student readability test with an average of 85% and also get an average of 97% from the teacher's perception test assessment. Keywords: android, e-Modul, wireless network DOI: http://dx.doi.org/10.23960/jpvti.v3.i2.202104